O uso de imagens térmicas na avaliação do risco de complicações do pé diabético - Zolet, Cerise Maria de Lima Soffiatti (2020)
Diabetes mellitus is a serious public health problem that can cause micro and macrovascular disorders. One of the most frequent complications is the appearance of foot ulcers, which can lead to the need for amputation. Changes in skin temperature are signs of abnormalities, and infrared thermography can be a useful tool in the early detection of the risk of diabetic foot ulcers. This examination captures the thermal radiation of the skin and provides an image with the temperature distribution, in a safe, fast and non-contact way. This work aimed to study the temperature distribution of the soles of diabetic and non-diabetic individuals. Seventy-two volunteers participated in the study, being 36 diabetic (10 men and 26 women) and 36 non-diabetic individuals (12 men and 24 women). Thermal images of the face and soles were acquired. The feet were then subjected to a cold stress test, after which a new thermal image was acquired. In statistical analysis, non-parametric tests were adopted. In the diabetic group, a negative correlation was obtained between age and forehead temperature (ρ= -0.492; p<0.01), and a positive correlation between forehead temperature and foot temperature, obtained before the thermal stress (ρ= 0.355; p<0.05). In the non-diabetic group, the correlation was positive between age and temperature of the eyes (ρ= 0.367; p<0.05), and negative between age and thermal asymmetry of the feet, before the cold stimulus (ρ= -0.365; p<0.05). There was no significant difference between the groups in the mean feet temperature. The analysis of thermal asymmetry between the feet revealed a significantly higher value (p<0.001) in diabetic individuals (0.74°C), than among non-diabetic volunteers (0.26°C). In the temperature difference between the heel and each toe, a significant difference was observed between the groups, and diabetic individuals showed the temperature of the toes much higher than that of the heel, especially in the hallux (1.7°C higher). The greatest temperature difference between the toes after the cold stress test was also significantly greater (p<0.001) in the diabetic group (1.85°C), than in the non-diabetic group (0.95°C). Based on these results, it is recommended to use thermographic analysis related to the temperatures of the toes (temperature difference between heel and toes and difference between toes), since the differences between the groups were significant, and the assessment can be made on each foot separately, without the need to compare corresponding regions of the two feet.